(untitled) (Research, Society and Development, 2021)
The pathogenic mechanisms that cause hypertensive crises are still unknown, however, there are causes that determine and facilitate their onset such as stress, poor nutritional conditions, black race, early reproductive life, socioeconomic status, obesity, smoking, diabetes mellitus, family history and high blood pressure. The aim of the study was to analyze the evidence available in the literature on the behavior of nurses in caring for pregnant women with gestational specific hypertensive syndrome (SHEG). This is an Integrative Literature Review study with descriptive and qualitative analysis, carried out in LILACS electronic databases and in SciELO and BVS electronic libraries. Primary studies that addressed the theme, produced in English, Portuguese and Spanish from January 2015 to July 2021 were included. Incomplete studies, duplicates and those in the private domain were excluded, making it impossible to read the entire study. It was evident that the actions performed by nurses are preventive activities such as early gestational follow-up, search for solutions to demands through the referral of RAS, identification of high levels of blood pressure in consultations, classification of prenatal care, among others. It is concluded that SHEG are aggravating factors for pregnant women, and may evolve into severe complications, such as the end of pregnancy, induction of urgent surgical delivery. It is noteworthy that the nurse is an indispensable and essential professional to offer comprehensive care for the health of pregnant women and management of hypertensive syndromes.